Clinical laboratory diagnostics in dentistry: Application of microbiological methods - Claesson, Rolf; Johansson, Anders; Belibasakis, Georgios N. (Frontiers in Oral Health, 2022)
Diagnosis and treatment in dentistry is largely based on clinical examination of the patients. Given that the major oral diseases are of microbial biofilm etiology; it can be expected that conventional microbial diagnostics could deliver supportive microbiological evidence to facilitate decision-making by the clinician. Applicable methods range from microscopy, to culture, to molecular techniques, which can be easily utilized in clinic laboratory environments proximal to the clinics, such as in academic Dental Institutions. Periodontal and endodontic infections as well as odontogenic abscesses are identified as conditions in which clinical microbiology laboratory analysis may be beneficial for the patient. Administration of antimicrobials agents, backed by microbiological analysis, can yield more predictable treatment outcomes in refractory or early occurring forms of periodontitis. Confirmation of a sterile root canal by means of a culture-negative sample during endodontic treatment may ensure the longevity of its outcome. Susceptibility testing on samples obtained from odontogenic abscesses may facilitate the selection of the appropriate antimicrobial treatment to prevent further spread of the infection.